Minería, sostenibilidad y seguridad alimentaria y nutricional en la población campesina en las veredas de San Miguel y El Peñón, municipio de Sibaté - Cundinamarca (2019)
The objective of this research work is to analyze the implications of the mining activity generated by the extraction of sand, in the rural population of El Peñón and San Miguel villages of the municipality of Sibaté, since the point of view of food and nutritional security, from a sustainability approach; for this a qualitative methodology was used. Among the main results, it is found that mining has a negative impact in ecosystem, economic and social terms on this peasant population, which directly undermines the right to food of their present and future generations. As protective elements in this theme, the importance of associativity is highlighted and the strengthening of capacities in the communities, as empowerment tools for the objective struggle of the defense of the territory. However, they are identified as unflattering factors as they are; the repression that is evident in the exercise of territory struggle, damage to peasant economies and the low social investment in the territories by the State. Likewise, a proposal for analysis is generated given the need to structure food and nutritional security from a sustainability approach, recognizing the breadth of the term environment. In conclusion it is recognized that mining in the rural population, not a model of their economic development identity, because of the struggle of resources between mining and agricultural activities.